Turbulence characteristics within the atmospheric surface layer of the coastal region of Qatar - Yuan Li (67017) (2022)
The atmospheric turbulence characteristics in the coastal region of Qatar are analyzed using the measurements conducted on the shoreline (26.08 N, 51.36 E). The micrometeorological data were collected, from August 2015 to September 2016, using sonic anemometers (20 Hz) at three heights and a weather station atop a 9-m tower. The turbulence characteristics are studied within the framework of Monin–Obukhov similarity theory (MOST), in the presence of the coastal inhomogeneities generated by the sea and land surfaces coming together. The results show the wind from the north-west prevails during the entire test period, with the wind speed higher than that from other directions. The non-dimensional standard deviations of velocity components are found to be consistent the results reported around the world and match suggested MOST scaling, with a relatively greater value for the dissipation rate of turbulent kinetic energy. The flux Richardson number shows a larger scatter under the super-stable and super-unstable regimes. Moreover, the non-dimensional standard deviation of temperature does not align with the suggested model under near-neutral and very stable regimes, and the gradient Richardson number shows some negative values under stable regimes. Two different atmospheric daily stability patterns, ‘orderly’ and ‘disheveled,’ are identified based on the wind conditions. The orderly stability pattern shows a daily descending and ascending trend during the sunrise and sunset periods, respectively, while the disheveled days follow a random pattern with no clear order. The two patterns are then related to the wind continuity and direction relative to the shoreline. Other Information Published in: Boundary-Layer Meteorology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s10546-022-00709-6